Pandangan Etika Terapan Kristen Tentang Kesetaraan Gender - Juriani Luther; Wahyu Wijiati (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
Gender equality remains a relevant interdisciplinary discourse in social, ethical, and theological contexts, particularly within societies influenced by patriarchal structures. This study examines the issue through the lens of Christian Applied Ethics using a qualitative literature review. The theological foundation of Imago Dei affirms the equal dignity and worth of men and women, challenging interpretations that restrict women’s participation in leadership, ministry, and public roles. Feminist theological ethics provide a critique of structures that sustain unequal gender relations, while biblical texts—particularly Genesis 1:27 and Galatians 3:28—affirm gender equality as consistent with God’s intention. The findings indicate that gender injustice is not rooted in Scripture but in cultural interpretations shaped by historical patriarchy. Therefore, Christian Applied Ethics requires structural transformation and the elimination of discriminatory systems to promote justice, equity, and inclusion